Atrial fibrillation after closure of patent foramen ovale in the REDUCE clinical study. Issue 5 (13th November 2021) - Andersen, Asger; Matzen, Kristina Laut; Andersen, Grethe; Settergren, Magnus; Sjostrand, Christina; Iversen, Helle K.; Roine, Risto O.; Hildick‐Smith, David; Spence, J. David; Rhodes, John F.; Kasner, Scott E.; Sondergaard, Lars; et al.
Abstract: Objectives: To describe the occurrence of postprocedural atrial fibrillation (AF) among patients with cryptogenic stroke undergoing patent foramen ovale (PFO) closure in the REDUCE clinical study and analyze for potential risk factors for the development of postprocedural AF. Background: AF is an adverse event that might potentially counterbalance the stroke prevention benefit from PFO closure. Data on AF after transcatheter PFO closure are sparse. Methods: We evaluated data from patients having PFO closure (Gore HELEX or Gore Cardioform Septal Occluder) in the REDUCE clinical trial ( n  = 408) in at post hoc explorative analysis. Median follow‐up was 5.0 years. Results: AF occurred in 30 patients (7.4%) after PFO closure with a total of 34 AF events. Most were reported as non‐serious (68%), detected within 45 days post‐procedure (79%), and resolved within 2 weeks of onset (63%). One subject with AF had recurrent stroke. Postprocedural AF occurred more frequently among subjects with higher age and large device sizes. Male sex was the only independent predictor of postprocedural AF. We found no association between the type of occluder (HELEX or Gore Cardioform Septal Occluder) or PFO anatomical characteristics and post‐procedural AF. Conclusion: In the REDUCE clinical study, postprocedural atrial fibrillation was mostly early onset, transient and with no later recurrence. Postprocedural AF occurred more frequently among patients with higher age and larger devices. Male sex was the only independent predictor of postprocedural AF.